2002
DOI: 10.1093/bja/89.5.702
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia: comparison of plain ropivacaine 5 mg ml-1 with bupivacaine 5 mg ml-1 for major orthopaedic surgery

Abstract: Intrathecal administration of either 17.5 mg plain ropivacaine or 17.5 mg plain bupivacaine was well tolerated and an adequate block for total hip arthroplasty was achieved in all patients. A more rapid postoperative recovery of sensory and motor function was seen in Group R compared with Group B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
73
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 16 publications
12
73
4
2
Order By: Relevance
“…However, in other studies no significant defference was foud in haemodynamics in both ropivacaine and bupivacaine groups when given intrathecally. [18][19][20][23][24][25] In present study no rescue analgesia was required in any of the patients in any group and quality of anesthesia obtained was adequate with both the groups. No signs of central nervous system toxicity (like restlessness, anxiety, incoherent speech, lightheadedness, dizziness, blurred vision, tremors, drowsiness, convulsions) or cardiovascular system toxicity (hypotension, bradycardia, hypertension, tachycardia, vasovagal reaction, arrhythmias like extra-systoles, atrial fibrillation, ST segment changes and myocardial infarction); severe allergic reactions (rash, itching, difficulty in breathing, tightness in the chest, swelling of the mouth, face, lips or tongue); nausea; vomiting noted in both groups.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, in other studies no significant defference was foud in haemodynamics in both ropivacaine and bupivacaine groups when given intrathecally. [18][19][20][23][24][25] In present study no rescue analgesia was required in any of the patients in any group and quality of anesthesia obtained was adequate with both the groups. No signs of central nervous system toxicity (like restlessness, anxiety, incoherent speech, lightheadedness, dizziness, blurred vision, tremors, drowsiness, convulsions) or cardiovascular system toxicity (hypotension, bradycardia, hypertension, tachycardia, vasovagal reaction, arrhythmias like extra-systoles, atrial fibrillation, ST segment changes and myocardial infarction); severe allergic reactions (rash, itching, difficulty in breathing, tightness in the chest, swelling of the mouth, face, lips or tongue); nausea; vomiting noted in both groups.…”
Section: Discussionmentioning
confidence: 73%
“…The findings correlate with the different studies. [17][18][19][21][22][23][24][25][26] The average highest level of sensory blockade which was achieved by giving either 3.5 ml of 0.75% isobaric ropivacaine or 3.5 ml of 0.5% hyperbaric bupivacaine was compared. The average highest level of sensory blockade in both the groups was T6 which was comparable (P=0.879).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 A recent clinical trial comparing levobupivacaine 0.5% with ropivacaine 0.5% for the management of postoperative ankle surgery pain found that levobupivacaine provide more long lasting postoperative analgesia compared with the same dose of ropivacaine, in contrast McNamee et al reported that intrathecal administration of 17.5 mg plain ropivacaine 0.5% or plain bupivacaine 0.5% resulted in similarly effective anesthesia for total hip arthroplasty. 2,3 We have planned the study to evaluate effect of plain ropivacaine 0.5% versus plain levobupivacaine 0.5% in gynecological surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…10 These findings are also consistent with various other studies conducted by Van Kleef et al, Gautier et al, Mc Namee et al, which state that ropivacaine has got lesser motor blockade due to its low lipid solubility resulting in lesser penetration of thick motor fibres. [9][10][11] The time taken for two segment regression of sensory blockade, total duration of sensory blockade and motor blockade were significantly prolonged in group B as compared to group A. This suggests that the duration of analgesia increases with increase in concentration of the drug.…”
mentioning
confidence: 99%